The comparative analysis of foreign and post-soviet studies on subjective well-being - Rizulla, A. R.; Tashimova, F. S. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
This paper shed light on the one of the actual problems of modern psychology, subjective well-being. This problem is one of the highest priorities for each government and society, which is actively in-vestigated by the science that offers a huge amount of concepts explaining this phenomenon. Taking into account the multiplicity of concepts there is a necessity of systemizing and integrating all these concepts that allows seeing the different perspectives of the studies and drawing a holistic view of subjective well-being phenomena. The foreign concepts are represented by M. Seligman’s subjective well-being formula that emphasizes the importance of an intentional activity in pursuing happiness. Another study made by F. Andrews and S. Withey emphasized the significance of personality type. R. Veenhoven offered the sig-nificance of positive emotions in subjective well-being. C. Ju and colleagues referred to emotional intel-ligence as a crucial factor that facilitates subjective well-being. Foreign scientists investigated subjective well-being from the different angles, paying attention to both internal and external factors and compo-nents that facilitates subjective well-being. On the contrast to foreign Russian scientists emphasized the importance of internal factors and resources such as resilience, meaning, resources and other. Finally, authors make a conclusion that illustrates the difference between foreign and post-soviet concepts. Key words: subjective well-being, happiness, positive emotions, life satisfaction.